P189 Mitochondrial dysfunction in muscle and airway compartments in COPD: preliminary findings. (14th November 2013) - Haji, G; Wiegman, C; Patel, M; Kemp, P; Adcock, I; Chung, F; Polkey, M
Abstract : Introduction & Rationale: Oxidative stress may underlie both pulmonary and non-pulmonary manifestations of COPD and may result from mitochondrial dysfunction. We hypothesised that if oxidative stress arose from the lung and 'spilled over' to cause non-pulmonary disease (e.g. skeletal muscle weakness) then greater evidence of mitochondrial dysfunction should be evident in the lung. Objectives: We measured mitochondrial function in endobronchial and skeletal muscle biopsies from COPD patients and healthy smokers matched for smoking history, age and sex. Methods and Measurements: We have so far biopsied 4 control smokers with normal FEV1 and FEV1 /FVC ratio, and 4 GOLD II COPD patients out of a planned total of 40. Bronchoscopy with endobronchial biopsies (EB) and percutaneous muscle biopsy of the vastus lateralis (VL) were obtained on the same day; additional phenotypic measurements included lung function, quadriceps strength and 6-minute walk (6MW) distance. Mitochondria were isolated and mitochondrial reactive oxygen species (ROS) and membrane potential (MP) were measured using MitoSOX Red and the carbocyanine dye JC-1 respectively and intracellular ROS determined by 2'-7'-dichlorofluorescin diacetate (DCF) staining. Results: GOLD stage II COPD patients had reduced lung function, quadriceps strength and 6MW test despite a similar smoking history. There was increased mitochondrial and intracellular ROS in both skeletal muscle and bronchial biopsies of COPD patients compared to controls. There was a trend for reduced MP in COPD EB mitochondria. Conclusion: The presence of excessive ROS in cells from a lung and a non-lung compartment support the existence of a generalised dysfunction of mitochondria in established COPD resulting in increased mitochondrial oxidative stress.